Strategi Coping Mahasiswa Dalam Menghadapi Stres Akademik - Alifia Salsabilla; Dini Rakhmawati; Chr. Argo Widiharto (INSIGHT: Jurnal Bimbingan Konseling, 2026)
Students often experience academic stres due to various demands of college, such as numerous assignments, pressure to achieve high grades, and tight deadlines for tasks. These conditions make it necessary for students to use coping strategies that can address the academic stres they experience. The aim of the research is to identify the more dominant and effective coping strategies used by students in dealing with academic stres. The research uses a non-experimental quantitative approach with a correlational research design. The research population consists of active 8th-semester students from the Guidance and Counseling Study Program at Universitas PGRI Semarang, totaling 115 students, with a research sample of 89 students. Data analysis used multiple linear regression. The research results show that the majority of students experience moderate levels of stres. The dominant coping strategy used by students is emotion-focused coping at 97.8%. The results of the regression test show that emotion-focused coping has a significant impact. Thus, emotion-focused coping becomes the more dominant and effective coping strategy used in dealing with students' academic stres.